Reading Autobiographical Comics : a Framework for Educational Settings. - Oppolzer, Markus (Frankfurt a.M. : Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2020)
This study updates reader-response criticism as the foundation of aesthetic reading in the classroom by bringing it in line with cognitive theories in literary studies and linguistics. Such a framework facilitates a consistent theoretical approach to autobiographical comics.
5.4 Autobiographical Selves -- 5.5 Embodiment &amp -- Enaction -- 5.6 Types of Autobiographical Comics -- Conclusion -- List of Illustrations -- Bibliography.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books